Decoding Virtual Employee Engagement: A Bibliometric Analysis - Pringgabayu, Dematria; Disman, Disman; Rofaida, Rofi (Universitas Batanghari Jambi, 2024)
This study investigates virtual employee engagement using a bibliometric analysis methodology. The objective of this study is to collect information and data pertinent to virtual employee engagement. In conducting this study, the researcher collected and extracted data from the Scopus database. In July 2023, a total of 933 articles were discovered in the Scopus database. After that, VOSviewer is used for scientific mapping and analysis of publication performance, including identifying the contributions of authors, journals, countries, and the number of author keywords. The quantity of publications has increased significantly over the years. Several countries have contributed to publications on virtual employee engagement. The United States contributes the most to this publication subject, followed by India, the United Kingdom, Australia, China, Malaysia, the Netherlands, Germany, Pakistan, and France. Based on article documents production, the Personnel Review